Low water availability and salinity effects on seedling viability of Bassia indica compared to B. iranica and B. prostrata (Amaranthaceae). Issue 1 (17th February 2016) - Shelef, Oren; Gendler, Tanya; Gutterman, Yitzchak; Rachmilevitch, Shimon
Abstract: Desert plants are exposed to water shortage and often salinity, instantly after dormancy withdrawal. We studied the effects of aridity and salinity on germination and initial growth of Bassia indica, B. iranica and B. prostrata . We hypothesized that: (1) all species would exhibit adaptations to water shortage immediately after germination, including rapid root growth and high seedling-survival rates; and (2) obligate halophytes benefit from positive effects of salinity on germination success and desiccation tolerance. After we germinated seeds in water or NaCl solutions, desiccated and rehydrated them, we found that all three species showed rapid germination and root elongation, as well as good germination success. However, salinity had a negative effect on the germination success of all three, with only B. indica germinating in 3% NaCl. Salinity had a positive effect on desiccation tolerance of B. indica seedlings, but had no significant effect on either B. prostrata or B. iranica . Thus the presence of salinity immediately after germination can protect halophyte seedlings from desiccation. To the best of our knowledge, survival of seedlings after periods of desiccation and rewetting with solutions of up to 3% NaCl has never been reported. Studying salinity tolerance in halophytes is important in a world exposed to expanding desertification.